Investment and Saving in China - Kuijs, Louis (World Bank, Washington, DC, 2012)
The author analyzes sectoral patterns of investment and saving in China-over time and compared with other countries-to shed light on the factors driving high investment and on how saving is channeled into investment. The findings inform several policy debates. Key findings include: (1) investment by enterprises distinguishes China from other countries and explains most of the variation over time; (2) high household saving explains only a part of the large difference in national saving between China and other countries-the majority is explained by high saving of the government and enterprises (through retained earnings); and (3) only about one-third of enterprise investment is financed via the financial sector, a lower share than in the early 1990s. The author also explores explanations behind high saving of the government and enterprises. His findings have three sets of policy implications. First, the identified financing patterns put in perspective the exposure of the financial sector to investment-related risks but, against a background of concerns about suboptimal allocation of capital, bring to the fore corporate governance, dividend policy, and transparency and accountability of public funds. Second, the findings suggest policy adjustments that would help in achieving the government's goals of improving the quality of growth and increasing the role of consumption. Third, long term saving prospects and the impact of financial sector and pension policies are discussed.